Person-Centered Long Term Services and Supports. (11th November 2018) - Calkins, M; Abushousheh, A; Chmielewski, E
Abstract: While the initial emergence and adoption person-centered care values and practices is several decades old, within the last decade it appears to have become more widely accepted, as evidenced by its frequency as a topic at conferences and references in the literature. But what precisely are these practices and how deep is the actual adoption? This session reports results of a study to evaluate the degree to which the long-term care field is familiar with and engaging in practices associated with person-centered care, and how the degree of adoption relates to various outcomes. This current study replicated and expanded upon the 2007 Commonwealth study, Culture Change in Nursing Homes: How Far Have We Come?; the results highlight the shifts in adoption over the past decade. New questions on environmental changes that reflect person-centered values were added to this survey, which was administered in both nursing homes and assisted living communities. Significant changes were reported in both familiarity with the concepts of person-centered care, as well as degree of adoption. Overall, the results indicate, almost without exception, more positive outcomes (satisfaction, clinical care, organization and operational outcomes) are associated with deeper adoption of person-centered care practices. Additional similar analyses explore the relationship between the CMS 5-star rating system person-centered care practices and outcomes.